2017
DOI: 10.1038/s41598-017-02127-y
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Intra- and Internetwork Functional Connectivity in Depressed Parkinson’s Disease

Abstract: Much is known concerning the underlying mechanisms of Parkinson’s disease (PD) with depression, but our understanding of this disease at the neural-system level remains incomplete. This study used resting-state functional MRI (rs-fMRI) and independent component analysis (ICA) to investigate intrinsic functional connectivity (FC) within and between large-scale neural networks in 20 depressed PD (dPD) patients, 35 non-depressed PD (ndPD) patients, and 34 healthy controls (HC). To alleviate the influence caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 75 publications
(120 reference statements)
1
27
0
Order By: Relevance
“…While there are quite a few PET and SPECT studies on depression in PD, functional connectivity MRI studies are relatively scarce. Previous functional connectivity studies have found in depressed PD patients an increased functional connectivity of the OFC 10 , inferior frontal gyrus 11 anterior cingulate 12 and posterior cingulate 13 , in accordance with our findings, in addition to decreased functional connectivity 12 , 13 , not identified here. We suggest that this may result from the substantial variability across studies in inclusion and exclusion criteria and statistical approaches.…”
Section: Discussionsupporting
confidence: 93%
“…While there are quite a few PET and SPECT studies on depression in PD, functional connectivity MRI studies are relatively scarce. Previous functional connectivity studies have found in depressed PD patients an increased functional connectivity of the OFC 10 , inferior frontal gyrus 11 anterior cingulate 12 and posterior cingulate 13 , in accordance with our findings, in addition to decreased functional connectivity 12 , 13 , not identified here. We suggest that this may result from the substantial variability across studies in inclusion and exclusion criteria and statistical approaches.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, Huang et al (2020) reported that the disrupted connection between the SN and ECN might contribute to depression in PD. Wei et al (2017) reported that the involvement of BGN, DMN, LFPN, and SN in PD facilitates the development of depression. Therefore, the impaired interactions between the triple network are critical for the occurrence and maintenance of depression in PD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the networks do not function independently, and investigation of the connectivity within one specific network may not be enough or may be somewhat unjustified. A study using independent component (IC) analysis (ICA) confirmed the involvement of BGN, DMN, left frontoparietal network (LFPN), and SN in depression in PD patients, facilitating the development of more detailed and integrative neural models of PDD ( Wei et al, 2017 ). Based on the above studies, we hypothesized that PDD may be related to the damage of specific large-scale neural networks, rather than on the disruption of a single, random, discrete brain region; not only the connectivity within these networks but also the coordination between them can be a prominent feature of PDD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, correlated with a reduced behavioral impairment, suggest compensatory mechanisms in PD patients with tremor (Vervoort et al, 2016). FOG is frequently associated with depression (Giladi and Hausdorff, 2006) and interestingly also depressive PD patients show increased FC in the left fronto-parietal network in addition to increased FC in basal ganglia and decreased FC in salience network and DMN (Wei et al, 2017). The authors also reported hyper-connectivity between the DMN and the left fronto-parietal network in depressed PD.…”
Section: Resting State Network In Functional Magnetic Resonance Imagingmentioning
confidence: 99%